Trust and beliefs among Europeans: Cross-country evidence on perceptions and behavior - Anja Dieckmann; Urs Fischbacher; Veronika Grimm; Matthias Unfried; Verena Utikal; Lorenzo Valmasoni (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Wirtschaftspolitik und Quantitative Wirtschaftsforschung (IWQW), 2015)
We conduct an experimental study among European citizens regarding cross-cultural perceptions related to trust in two dimensions: volunteerism and honesty. We use representative samples from five major economies of the Euro area: France, Germany, Italy, the Netherlands, and Spain. We find that European citizens rely on nationality to infer behavior. Assessments of behavior show a north/south pattern in which participants from northern countries are perceived to be more honest and to provide more effort in a volunteering game than are participants from southern countries. Actual behavior is, however, not always in line with these assessments. Assessments of honesty show strong evidence of social projection: Participants expect other European citizens to be less honest if they are culturally closer to themselves. Assessments of volunteerism instead show a similar north/south-pattern in which both northern and southern Europeans expect higher performance of northerners than they do of southerners.
Keywords: D82; D84; C93; Z13; 330; Cross-cultural perceptions; Europe; Honesty; Real effort; Representative experiment